Advancing Circular Economy in Olive Oil Production: Comparing Maturation Systems for Vermicompost Creation from Olive Pomace - Giulia Angeloni; Agnese Spadi; Ferdinando Corti; Marco Calcaprina; Giulia Carpi; Francesco Maioli; Alessandro Parenti; Piernicola Masella (Biomass)
The production of extra virgin olive oil (EVOO) creates by-products like olive pomace, which brings environmental issues due to its strong odors and the challenges involved in storage. To address this within a circular economy framework, this study explores the potential of olive pomace as a nutrient source for earthworms, aiming to transform it into a beneficial soil amendment. Key nutrients in the pomace, such as polyphenols, sugars, and organic matter, were examined for their effectiveness in nourishing earthworms. Four distinct treatments were applied to the pomace: mechanical mixing, aeration, a combination of both, and no treatment. For a period of 30 days, chemical parameters including pH, polyphenol levels, and moisture content were monitored, while earthworm preferences were assessed at Centro Lombricoltura Toscano (CLT). The study revealed significant differences in the chemical composition of the pomace depending on the treatment, especially regarding polyphenol and total sugar content. These changes influenced the palatability for earthworms, with the combined treatment producing the most appealing pomace, likely due to the increased nutrient availability. Ultimately, olive pomace has promising potential to be repurposed into a nutrient-dense soil amendment, alleviating environmental concerns and contributing to more sustainable waste management within the olive oil industry.